Stress Relaxation and Composition of Hydrazone‐Crosslinked Hybrid Biopolymer‐Synthetic Hydrogels Determine Spreading and Secretory Properties of MSCs. Issue 14 (26th May 2022) - Borelli, Alexandra N.; Young, Mark W.; Kirkpatrick, Bruce E.; Jaeschke, Matthew W.; Mellett, Sarah; Porter, Seth; Blatchley, Michael R.; Rao, Varsha V.; Sridhar, Balaji V.; Anseth, Kristi S.
Abstract: The extracellular matrix plays a critical role in mechanosensing and thereby influences the secretory properties of bone‐marrow‐derived mesenchymal stem/stromal cells (MSCs). As a result, interest has grown in the development of biomaterials with tunable properties for the expansion and delivery of MSCs that are used in cell‐based therapies. Herein, stress‐relaxing hydrogels are synthesized as hybrid networks containing both biopolymer and synthetic macromer components. Hyaluronic acid is functionalized with either aldehyde or hydrazide groups to form covalent adaptable hydrazone networks, which are stabilized by poly(ethylene glycol) functionalized with bicyclononyne and heterobifunctional small molecule crosslinkers containing azide and benzaldehyde moieties. Tuning the composition of these gels allows for controlled variation in the characteristic timescale for stress relaxation and the amount of stress relaxed. Over this compositional space, MSCs are observed to spread in formulations with higher degrees of adaptability, with aspect ratios of 1.60 ± 0.18, and YAP nuclear:cytoplasm ratios of 6.5 ± 1.3. Finally, a maximum MSC pericellular protein thickness of 1.45 ± 0.38 µm occurred in highly stress‐relaxing gels, compared to 1.05 ± 0.25 µm in non‐adaptable controls. Collectively, this study contributes a new understanding of the role of compositionally defined stress relaxation on MSCs mechanosensing and secretion. Abstract : In this work, a stress‐relaxing hydrogel is tuned to investigate the impact of controlled variations in stress relaxation timescales on mesenchymal stem/stromal cells (MSCs). Specifically, a hybrid network, containing both biopolymer and synthetic macromer components is synthesized to examine MSCs mechanosensing and secretory properties as a function of stress relaxation. Scale Bar = 50 µm.